THE OIL INDUSTRY IN KAZAKHSTAN - Yermekova A.S; Karimbaeva Zhanbike; Utegenova Zamira; Urazalieva Ayida (Foundations and Trends in Research, 2024)
This article examines the oil industry in Kazakhstan. Oil fields and their production. Kazakhstan’s oil industry remains an important component of the economy and the global market. Kazakhstan is one of the world’s oil producing countries. Oil production in Kazakhstan began at the end of the XIX century, much earlier than in Iran, Kuwait, Mexico, Norway, Saudi Arabia. The Russian military, travelers and scientists were the first to note the high probability of finding industrial oil reserves in this region. The Government of Kazakhstan has high hopes for the North Caspian project, namely Kashagan. With the start of commercial production of Kashagan, Kazakhstan will enter the top 5 largest oil producers in the world.